1982
DOI: 10.1002/path.1711360104
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin alters behaviour of isolated osteoclasts

Abstract: Osteoclasts were incubated on a glass or plastic substrate and the effect of calcitonin (CT) on their behaviour was observed. Before exposure to CT the osteoclasts were actively motile, the cytoplasm advancing behind broad pseudopodial (lamellipodial) processes which showed intense ruffling activity. CT caused cessation of lamellipodial activity within minutes, followed by gradual fragmentation and retraction of lamellipodia. Complete osteoclast quiescence was regularly induced by concentrations of CT above 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
210
1
4

Year Published

1989
1989
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 495 publications
(219 citation statements)
references
References 10 publications
4
210
1
4
Order By: Relevance
“…The cells were then incubated for 5min, 10min, 30 min, 1 h and 2 h before formalin fixation for staining (Giemsa). The effectiveness of the CT used in this experiment to inhibit osteoclast motility and induce the characteristic change in osteoclast morphology was confirmed by adding the same CT solution to neonatal rodent osteoclasts which had been isolated in a similar manner as previously described (Chambers & Magnus, 1982).…”
Section: Preparation Of Isolated Giant Cellsmentioning
confidence: 56%
See 1 more Smart Citation
“…The cells were then incubated for 5min, 10min, 30 min, 1 h and 2 h before formalin fixation for staining (Giemsa). The effectiveness of the CT used in this experiment to inhibit osteoclast motility and induce the characteristic change in osteoclast morphology was confirmed by adding the same CT solution to neonatal rodent osteoclasts which had been isolated in a similar manner as previously described (Chambers & Magnus, 1982).…”
Section: Preparation Of Isolated Giant Cellsmentioning
confidence: 56%
“…However, bone resorption by OMGCs significantly differs from that of isolated osteoclasts in that it is directly stimulated by PTH and not inhibited by calcitonin McSheehy & Chambers, 1986a,b). PTH stimulation of osteoclastic bone resorption has only previously been seen when osteoclasts are incubated in the presence of osteoblasts, and osteoclastic bone resorption is also directly inhibited by calcitonin, a feature which is reflected by the characteristic change in the shape of the cell (Chambers & Magnus, 1982). This morphological response to calcitonin was not exhibited by OMGCs isolated in shortterm cultures on coverslips.…”
Section: Discussionmentioning
confidence: 89%
“…The most characteristic features of osteoclasts are the presence of ruffled borders and sealing zones. The sealing zones serve to attach osteoclasts to the bone surface and isolate the resorption areas from the surrounding areas (Chambers and Magnus 1982;Väänänen et al 2000). It has been reported that disruption of the sealing zones suppresses the boneresorbing activities of osteoclasts (Lakkakorpi and Väänänen 2004;Nakamura et al 1991;Suzuki et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike osteoclasts, they were TRAP negative, CD14 positive (Athanasou & Quinn, 1990) and did not respond morphologically to calcitonin (Chambers & Magnus, 1982). No multinucleated cells were present amongst the isolated cells.…”
Section: Resultsmentioning
confidence: 92%
“…Cells cultured on glass coverslips for similar periods were assessed for several osteoclast characteristics viz. morphological response to salmon calcitonin (Rorer Pharmaceuticals, UK) 1 tg ml-' (Chambers & Magnus, 1982), acid phosphatase (AP) and tartrate-resistant acid phosphatase (TRAP) staining (Minkin, 1982) as well as indirect immunoperoxidase staining for CD14 (UCHMI) and CD68 (EBM/1 1) (Athanasou & Quinn, 1990) (macrophage-associated antigens) and epithelial cytokeratin (LP34) (Dakopatts a/s).…”
Section: Methodsmentioning
confidence: 99%